2017
DOI: 10.4172/2157-7439.1000167
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Electrical Characteristics of Au/N-Si Schottky Diodes, with and Without Bi-Doped PVA Interfacial Layer in Dark and Under Illumination at Room Temperature

Abstract: In order to see the effect of Bi-doped PVA interfacial layer on electrical characteristics, both Au/n-Si (MS) and Au/Bidoped PVA/n-Si (MPS) type Schottky barrier diodes (SBDs) were fabricated, and their main electrical parameters were investigated using current-voltage (I-V) and capacitance-voltage (C-V) measurements, in dark and under illumination at room temperature. Forward bias semi-logarithmic I-V plots of these SBDs show two distinct linear regions, with different slopes in the low and intermediate volta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…(1), and the reverse fit is to Eq. (10) values also while considering the thermionic emission equation, without which unreliable values of n and I 0 are obtained. Hence, the term V in Eq.…”
Section: Current-voltage Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1), and the reverse fit is to Eq. (10) values also while considering the thermionic emission equation, without which unreliable values of n and I 0 are obtained. Hence, the term V in Eq.…”
Section: Current-voltage Characteristicsmentioning
confidence: 99%
“…This leads to Fermi level pinning, thereby reducing its performance drastically and limiting its application to be used as tailor-made devices. However, the presence of an interfacial layer between the metal contact and the semiconductor can lead to change in band alignment by changing the barrier height (BH) [2,[10][11][12][13][14]. This change is related to many parameters such as the type of the chosen organic compound and its formation, its thickness, the process of surface preparation, the impurity concentration of a semiconductor and the interfacial layerinduced dipole at the M-S interface [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of a device measured only at room temperature or over a narrow range of temperatures cannot yield detailed information on the conduction mechanism and the nature of BH at the M/S interface. These measurements, when carried out over a wide temperature range, better reveal various aspects on the conduction mechanism and the nature of BH [10][11][12][13][14]. Many previous studies have found increases in the BH and decreases in n with increasing temperature [4][5][6][7][8][10][11][12][13][14][15][16], in disagreement with the predictions of the standard TE theory of temperature-independent BH and ideality factor.…”
Section: Introductionmentioning
confidence: 53%
“…These measurements, when carried out over a wide temperature range, better reveal various aspects on the conduction mechanism and the nature of BH [10][11][12][13][14]. Many previous studies have found increases in the BH and decreases in n with increasing temperature [4][5][6][7][8][10][11][12][13][14][15][16], in disagreement with the predictions of the standard TE theory of temperature-independent BH and ideality factor. In the last two decades, both the abnormal behaviour of the BH and the nonlinearity of the Richardson plot have been observed [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation